Antifungal Carvacrol Loaded Chitosan Nanoparticles - Alberto Vitali; Annarita Stringaro; Marisa Colone; Alexandra Muntiu; Letizia Angiolella (MDPI AG, 2021)
The increased prevalence and incidence of fungal infections, of which Candida albicans represents one of the most life-threatening organisms, is prompting the scientific community to develop novel antifungal molecules. Many essential oils components are attracting attention for their interesting antifungal activities. Given the chemical and physical characteristics of these compounds, the use of appropriate nanodelivery systems is becoming increasingly widespread. In this study, chitosan nanoparticles were prepared using an ionic gelation procedure and loaded with the phenolic monoterpene carvacrol. After a bioassay guided optimization, the best nanoparticle formulation was structurally characterized by means of different spectroscopic (UV, FTIR and DLS) and microscopy techniques (SEM) and described for their functional features (encapsulation efficiency, loading capacity and release kinetics). The antifungal activity of this formulation was assayed with different Candida spp., both in planktonic and biofilm forms. From these studies, it emerged that the carvacrol loaded nanoparticles were particularly active against planktonic forms and that the antibiofilm activity was highly dependent on the species tested, with the C. tropicalis and C. krusei strains resulting as the most susceptible.